Impact of Fluoxetine Treatment and Folic Acid Supplementation on the Mammary Gland Transcriptome During Peak Lactation - Celeste M. Sheftel; Celeste M. Sheftel; Lihe Liu; Sena L. Field; Samantha R. Weaver; Chad M. Vezina; Francisco Peñagaricano; Laura L. Hernandez; Laura L. Hernandez (Frontiers Media S.A., 2022)
Serotonin is a key regulator of mammary gland homeostasis during lactation. Selective serotonin reuptake inhibitors (SSRIs) are commonly used to treat peripartum depression, but also modulates mammary gland serotonin concentrations and signaling in part through DNA methylation. The objective of this study was to determine mouse mammary transcriptome changes in response to the SSRI fluoxetine and how methyl donor supplementation, achieved by folic acid supplementation, affected the transcriptome. Female C57BL/6J mice were fed either breeder diet (containing 4 mg/kg folic acid) or supplemented diet (containing 24 mg/kg folic acid) beginning 2 weeks prior to mating, then on embryonic day 13 mice were injected daily with either saline or 20 mg/kg fluoxetine. Mammary glands were harvested at peak lactation, lactation day 10, for transcriptomic analysis. Fluoxetine but not folic acid altered circulating serotonin and calcium concentrations, and folic acid reduced mammary serotonin concentrations, however only fluoxetine altered genes in the mammary transcriptome. Fluoxetine treatment altered fifty-six genes. Elovl6 was the most significantly altered gene by fluoxetine treatment along with gene pathways involving fatty acid homeostasis, PPARγ, and adipogenesis, which are critical for milk fat synthesis. Enriched pathways in the mammary gland by fluoxetine revealed pathways including calcium signaling, serotonin receptors, milk proteins, and cellular response to cytokine stimulus which are important for lactation. Although folic acid did not impact specific genes, a less stringent pathway analysis revealed more diffuse effects where folic acid enriched pathways involving negative regulation of gene expression as expected, but additionally enriched pathways involving serotonin, glycolysis, and lactalbumin which are critical for lactation. In conclusion, peripartal SSRI use and folic acid supplementation altered critical genes related to milk synthesis and mammary gland function that are important to a successful lactation. However, folic acid supplementation did not reverse changes in the mammary gland transcriptome altered by peripartal SSRI treatment.